A Comparative Study of NGOs Movements for Sustainable Environmental Development in Thailand and Indonesia - คำดีเกิด, รจนา (Local Administration Journal, 2018)
This research aimed to study and compare the environmental movements of NGOs in Thailand and Indonesia, and to find alternative ways for sustainable management. It employed a documentary research method. It is found that environmental problems in Thailand and Indonesia are similar in that both their economic development approaches have caused negative impacts on the environment. NGOs take their role in mobilizing and raising these issues to the public by applying two key tactics: a conventional approach and a disruptive one. Eight means that bring about sustainability are: community-based forest management, application of local knowledge in communities, restoration of traditional wisdoms in resource management, formation of the youth groups for natural conservation, organization of forum for learning and exchanging information on the environment, establishment of networks for mobilizing environmental issues, provision of information on the environment to the policy makers, and communication of environmental issues to people to raise their awareness on those environmental problems.